MAKROZOOBENTOS COMMUNITY STRUCTURE IN THE INTERTIDAL ZONE OF THE SIRANDAH ISLAND OF CITY PADANG WEST SUMATERA PROVINCE - Ivyna Clarisa Tampubolon; Afrizal Tanjung; Syafruddin Syafruddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMacrozoobentos is one of the important groups in aquatic ecosystems due to its role as a key in the food network. This research was conducted in the waters of Sirandah Island, Padang City, West Sumatera Province in Juli 2018, aiming to know macrozoobentos community structure which includes: type, abundance, relative abundance, index of species diversity, uniformity index, dominance index and distribution pattern. Sampling using line transect method was done on 4 stations. The results of the study found 2 classes of macrozoobentos with 7 species, where the value of macrozoobentos abundance obtained ranged from 0.056 to 0.806 ind/m2. Diversity (H’) of species was ranged from 0.33 to 2.69  was relatively medium, while the value of uniformity index (E)  ranged from 0.18 to 1.19.While the value of the dominance index (C) ranged from 0.12 to 0.34 and the value of the distribution pattern (Id) ranges was in groups from 0.09 to 3.6. Keywords: Community Structure, Makrozoobentos, Intertidal Zone, Sirandah  Island